Exploring Maxillary Sinus Ostium Characteristics and Insights for Pathology Prediction and Anatomical Variations: A Cone Beam Computed Tomography (CBCT) Analysis: Maxillary sinus characteristics according to CBCT - Valizadeh, Solmaz; Ghazizadeh Ahsaie, Mitra; Fotuhi Firoozabad, Farnaz; Aryanezhad, Seyed Sasan; Arianezhad, S. Marjan (Journal of Dental School, 2025)
Objectives: Understanding the anatomy of the maxillary sinus is essential for ensuring a successful surgical procedure. This study utilized CBCT to evaluate the relationship between maxillary sinus ostium characteristics, adjacent anatomical structures, and pathologies. Methods: A retrospective evaluation was conducted on CBCT images of 400 maxillary sinuses. Measurements included the height and dimensions of the ostium, as well as the length of the infundibulum. The study investigated maxillary sinus pathologies, anatomical variations, and the associations between the characteristics of the maxillary sinus ostium and adjacent anatomical structures. Statistical analyses were performed using Pearson’s Chi-Square test, simple logistic regression, multiple logistic regression, and multiple linear regression models at p<0.05. Results: The mean ±SD for ostium height, size of the ostium entry, and infundibulum length were 31.08±4.99mm, 1.72±2.03 mm, and 7.81±1.73 mm, respectively. An increase in Haller cell and infundibulum length raised the risk of a mucosal membrane in the ostium area. The Ostium height was significantly higher in males (P<0.05). Mucosal thickening (MT) was considerably higher in patients with positive maxillary sinus septum (P<0.005). Infundibulum length, nasal septum deviation, and Haller cell significantly affected sinus opacity rate (P<0.001). In cases where the deviation was towards the sinuses, maxillary sinus pathologies occurred more frequently. Age and gender significantly affected MT, the mucous membrane in the ostium, and at least one sinus pathology (P<0.05). Conclusion: Maxillary sinus pathologies can be evaluated by increasing the infundibulum length and reducing the ostium size. CBCT evaluation is crucial for successful surgery and preventing complications. Accurate assessment of sinuses and nasal passages in the elderly is recommended.